USING WHATSAPP MESSENGER AS AN INTERPERSONAL COMMUNICATION MEDIA BETWEEN PARENTS AND TEACHERS IN INFORMING CHILDREN'S LEARNING ACTIVITIES AT SCHOOL - Meisyaroh, Siti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
This research concerns the use of the